Neuroprotection of medial septal cholinergic neurons by memantine after intralateral septal injection of Aβ1–40. Issue 8 (27th May 2015) - Castaneda, Maria T.; Lopez, Erick D.; Touhami, Ahmed; Tovar, Ramiro; Ortega, Miriam R.; Rodriguez, Jose M.
Abstract : Alzheimer's disease (AD) is a progressive disorder of the brain that leads to memory loss, dementia, and death. Several lines of evidence suggest that the accumulation of amyloid-β (Aβ) peptides may trigger the dysfunction and degeneration observed in the AD brain. The basal forebrain, including the septal region, which regulates the excitability of the hippocampus and neocortex, is affected early in AD because its neurons are vulnerable to Aβ peptides. In addition, connections between lateral and medial septal regions (medial septum and diagonal band of Broca) have been demonstrated in previous studies. To demonstrate the involvement of excitotoxicity in Aβ-induced septal damage, we compared rats injected with Aβ1–40 into the lateral septal region structure with rats treated with memantine (a noncompetitive NMDA receptor antagonist), before, during, and after Aβ1–40 injection. Medial septal cholinergic neurons were immunochemically identified and their numbers were estimated using Image J cell count. Our results show that Aβ1–40 -treated animals have a significantly low number of medial septum and diagonal band of Broca cholinergic neurons compared with the Aβ/memantine-treated group.